Institutional Policy in Land Procurement Under The Omnibus Law Regime - Kuswahyono, Imam; Ula, Hikmatul (Brawijaya Law Journal, 2020)
The legal culture procedure with socio-legal analysis will be able to answer the fundamental questions in the problems of practices of land procurement for public interests, in particular the issue of compensation. The crucial issue of compensation within the implementation of the policy of land procurement regards the non-equivalence of land value, both utility value and economic value of structures and landscapes, to the monetary compensation. The use of the legal culture approach is to provide answers and implement them to resolve issues of land procurement for public interests in the omnibus law regime to maintain justice to landowners and preserve the environment. The correlation of the cultural approach and activities of land procurement is that culture refers to the target of the national conscience, and the cultural approach based on the growth mindset will result in wisdom and nobility of the decisions of public officials to prioritize the people rather than interests of investment. The government must choose to renegotiate the policy of enacting the Law of Employment Creation, which is judged by the greater public to conflict with the spirit and mandate of the Preamble and contents of the 1945 Constitution. It needs renegotiation between the state and people by discussing in-depth the legal substance of the law is not performed, and then the law in question must have its enactment firmly rejected.